Pembelajaran Qur’an Hadits di MI YAPPI Ngunut - nurhayati, Ria; ., Solehudin; Hayati, Nur Rohmah (STAINU Purworejo, 2023)
This article aims to discuss the learning of the Al-Qur'an Hadith in madrasah ibtidaiyah which focuses on two stages of learning, namely planning and implementation. In addition to planning and implementation, this study discusses how the duties and roles of teachers in the teaching and learning process, and how teacher creativity is used, in teaching and learning activities there are several methods, namely the lecture method, the question and answer method, the discussion method, the assignment method, the work method. group. This study used data collection including: literature and field studies. This field research uses observation and interview techniques. Based on the research results, it can be concluded that Al-Qur'an Hadith learning at MI YAPPI Ngunut started in Learning planning activities at MI YAPPI Ngunut were carried outwell because the teachers understand the 2013 curriculum and design it RPP, then the RPP is applied as a reference for KBM (activities teaching and learning) and developed by the teacher of the subject, through various applied methods. Learning evaluation is important because it is the final stage from the learning process. This is in line with Popham's view that assessment plays a big role in determining success education